Building a Common State Army Forces in Post-War Bosnia-Herzegovina: Assessing its Peace-Building Perspective - Bedrudin Brljavac (Romanian Journal of European Affairs)
When the war in Bosnia ended in December 1995 with the Dayton Agreement, the armed forces in the country were divided along the ethnic lines. However, in 2005 the country’s politicians agreed on defence reforms that led to merging former rival armed forces into a unified army of BiH as a condition for Bosnia to join NATO. Thus, today unified BiH army is making small but significant contributions towards security maintenance both at national and global level. In order to explain efforts of Bosnian politicians to bring the country into the Euro-Atlantic structures and send their troops into multi-national missions we have used the security community theory coined by Karl Deutsch. Thus, NATO-related reforms have strengthened security and peace-building attempts among the former warring ethnic groups. Also, the country’s participation in multi-national peace missions abroad has been a crucial commitment to the world security and peace. Thus, today as a NATO aspirant Bosnia has practically become a country that exports security.